Exploring an art photography movement in Malaysia (1900-2000) / Raziq Abdul Samat...[et.al] - Abdul Samat, Raziq; Wan Mohd Zain, Wan Nor Ayuni; Shaari, Shafirah; Madon, Dona Lowii; Alias, Aidah; Abd Ghapur, Mohd Fakhrul Rodzi (2016)
Photography lives between art and sciences. Photography has been developed since 1827 when Joseph Nicephore Niepce who invented the first permanent image in a world entitled 'A View From Windows at Le Gras'. After the achievement of creating permanent image, there are several enhancement of experiments has been done image such as Dagguereotype (1839), Calotype (1841), Wet Collodion (1851) and many more. The widespread of photography to the world started in 1888 when George Eastmen introduced Kodak box camera with dry plate of roll film. Along this achievement it created a job and also a photography movement. There are several an art photography movement in 19th century started with Pictorialism, Russian Constructivism, Dadaism, Surrealism, Straight Photography, California Modernist, Abstract Photography Post WWII and Post Modernist.Objectively this research paper is to explore an art photography movement in Malaysia which of these movements was influenced Malaysian art photographers from 1900 to 2000.